PERANCANGAN ARSITEKTUR SISTEM INFORMASI MANAJEMEN PENYELESAIAN LAPORAN (SIMPeL v.3.0) DI OMBUDSMAN REPUBLIK INDONESIA - Tulus Pribadi; Syahrizal Dwi Putra (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
The Indonesian Ombudsman is a State Institution tasked with overseeing public services based on Law Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia. Based on this task, the Ombudsman of the Republic of Indonesia performs services in the form of receiving reports / complaints from the public regarding public services performed by service providers that must be resolved quickly and efficiently. To achieve this goal, the Ombudsman of the Republic of Indonesia must have an integrated Information System that can record and complete the report completion process. Taking into account the magnitude and complexity of the work in the Ombudsman of the Republic of Indonesia, the Management Information System for Completion of this Report must be well planned and based on the data needed by each user. The Architecture of the Management Report Management Information System Completion of the Community Report was built using the enterprise architecture planning model approach, especially the TOGAF ADM method with the hope that the SIMPeL v3.0 blueprint can be the basis for the development of the Report Settlement Management Information System (SIMPeL v3.0) in the Ombudsman of the Republic of Indonesia.